THE EFFECT OF USING CLUSTERING TECHNIQUE ON STUDENTS’ACHIEVEMENT IN WRITING NARRATIVE TEXT - Madina madin (elt, 2020)
This research presents a research report on students’achievement in writing narrative text by using clustering technique between two groups: experimental and control group. The design of this study is experimental group. The population of this study is eleven grade students of SMK Sandhy Putra 2 Medan in the academic year 2017/2018. The samples of this research were the students of Class X-TKJ1and TKJ2 consisting 31 students as the experimental group, and Class X-TB1 and X-TB2 consisting 31 students as the control group. The data of the test were analyzed by using t-test formula to know the difference of the students’ achievement in writing narrative text. In the pre-test the mean of score of the experimental group 62,93 and the mean of post test of 79,54 and the control group is 61,23 and the post-test 51,06 the results of the t-test 6,10>2,000 Key Words : Clustering technique, Narrative text